PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI KHUSUS TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA SELATAN - fharaztiwi, Fujiati putri (Jurnal Ilmu Ekonomi, 2025)
The aim of this research is to determine the effect of Regional Original Income (PAD) and Special Allocation Funds (DAK) on Economic Growth in South Sumatra Province in 2014-2023. The research was conducted in the South Sumatra region using secondary data from the Central Statistics Agency (BPS) for 2014-2023. The model in this research focuses on regression analysis. Data analysis was carried out using Multiple Linear Regression Analysis. Based on the research results, it shows that PAD has a positive and significant effect on Economic Growth in South Sumatra 2014-2023. Meanwhile, DAK has a positive and insignificant effect on economic growth. Keywords: Regional Original Income, Special Allocation Funds And Economic Growth